The Use of Rasa ‘To Feel’ as a Hedge in Appraisaltheory: A Corpus Study - Karisma Tarigan; Margaret Stevani (International Journal of English and Applied Linguistics (IJEAL), 2021)
The word rasa 'to feel' or 'to taste' in Indonesian was usually used to show a feeling or taste. It concerned as a hedge or a word whose function was to make things fuzzier or less fuzzy. Through this study, the writers aimed at describing the use of ‘rasa’ as a hedge through corpus study derived from Indonesian novels. To analyze the data, the write applied appraisal theory that classified the assessment of language into three categories, that were affect, judgment, and appreciation by using descriptive qualitative method. The result of the study showed that rasa 'to feel' was used as a hedge for judgment, affects, and appreciations. The result indicated that Indonesian were more careful when they gave comments on whether someone was good or bad or whether what they met or violated some social standards and did not need to when they talked about someone's feeling or gave appreciation.